Digital and Operational Advancement in Construction Logistics A Case Study of Construction Logistics Management at BRA - SÄRNSTRÖM, ALEXANDRA; WESSMAN, EDVIN (My University, 2023)
Construction logistics management (CLM) and construction supply chain management (CSCM) are crucial for the construction industry’s performance progress and potential improvement of production efficiency. Research shows that construction logistics largely affect the overall project costs and have a significant impact on environmental performance and the health and safety of both employees and civilians in urban settings. While previous research has shown clear benefits for contractors following the advancement of CLM, it is yet to provide a comprehensive understanding of how digital tools should be implemented successfully. Furthermore, there is limited research on how digital tools may alter or aid the construction logistics efficiency on the building site. The aim of the thesis is to identify the benefits and challenges of an increased level of digitalization in construction logistics at BRA, and in doing so, provide recommendations for the use of digital tools for logistics activities in current and future projects. The aim was pursued through a case study of three ongoing construction projects at BRA with various levels in the use of digital tools for construction logistics. The study entails on-site observations and 16 semi-structured interviews with actors affected by or involved in construction logistics. An abductive research process allowed for the iterative development of theory and empirical data, which was analyzed using an analytical framework. The study shows that well-functioning construction logistics can contribute to monetary gains and improved production performance. However, these values are difficult to measure and are therefore often overlooked by practitioners who tend to focus on the challenges of implementing and maintaining CLM and CSCM instead. These challenges generally boil down to organizational preconditions and work culture in the construction industry, as well as the limited knowledge and competence within construction logistics. In conclusion, early involvement of construction logistics planning facilitates the implementation of digital tools in production. In every project, BRA should assign explicit responsibility for construction logistics to a specific person or team and utilize digital delivery management systems to increase coordination between actors on site and suppliers and decrease the frequency of unplanned events. Task distribution tools should be utilized in projects with dedicated logistics workers, as they provide a better overview, allowing more accurate in-depth planning and reducing collisions in the schedule during the production phase. To promote the advancement of construction logistics management in the early phases of the construction process, BRA needs to consider the project-specific preconditions and plan the logistics activities thereafter. Lastly, the study concludes that evaluation methods are needed to identify the extent of indirect and intangible benefits that digital tools for construction logistics can bring.
Keywords: construction logistics, construction logistics management, construction industry, supply chain management, digitalization, digital tools.